Assessment on production quality of traditional Singgora tiles in Malaysia / Nor Hidayah bt Abdullah - Abdullah, Nor Hidayah (2014)

(untitled)
Most users, including the conservators, have no confidence in using Singgora roofing tiles due to their low quality. This phenomenon has caused the Singgora tile industry to become declined and most of the new generation are not aware of the existence of this traditional craft in Malaysia. Based on the comments that often arise regarding this handmade tile, this study was carried out with the aim to improve the quality of Singgora tiles based on the traditional manufacturing method by the local factory in Kelantan. The methodology that used for this research was case study and experimental works. The data in the case study was collected by observing the manufacturing process in the factory in order to identify the factors that affect the quality of Singgora tiles. Besides, the experimental works was conducted to measure the properties of existing factory product and to investigate the effect of firing condition and impurities on the properties of Singgora tiles. For existing factory product, the tests conducted were the surface quality, dimensional accuracy, percentage and types of impurities, grade of sand in Bris clay, water absorption and flexural strength test while the tiles that fired at various conditions in the laboratory were subjected to water absorption and flexural strength test. The study found that the quality of existing factory product is low due to the poor quality control in all stages of production. The results of experimental works for samples fired at varying firing temperature and time show the quality of Singgora tiles is significantly improved by firing at higher temperature and longer duration. In addition, the effect of impurities in the untreated clay is decreased and the reliability of the product is increased with the increased of firing temperature and firing time. It was iv concluded that the optimum mechanical strength for Singgora tiles within the temperature range considered is obtained at 1050ºC for 4 hours or 900ºC for 6 hours. Based on the finding of this research, it is suggests that the manufacturing process of Singgora tiles is conducts under quality control. It is important in producing greater surface quality of Singgora tiles with uniform size of product. Besides, the strength of Singgora tiles can be improved by prolongs the timing of firing process using traditional kiln in the factory.